Modeshow 1994. - ICC (Internationaal Cultureel Centrum), Antwerpen (Antwerpen : Koninklijke Academie voor Schone Kunsten, 1994)
Schmidt-Thomsen, Valeska ; Broich, Christoph ; Hamaïde, Sophie ; Ernst, Henriette ; Devos, Mariëlle ; van den Hout, Monique ; Yearwood, Kentroy ; Feriani, Souâd ; Schneider, Stephan ; Vandevorst, Nico.
ICC, Antwerpen, 21 juni - 3 juli 1994
kunstcatalogus